Association of Ambient Air Quality with Male’s Pulmonary Function in Kolkata City, India - Chatterjee, P; Das, P (Kathmandu University Medical Journal, 2015)
Background Kolkata is one of the polluted metropolitan cities in India where health effects of air pollution are raising serious concern. Objectives Purpose of the present study was to analyze association between levels of air pollutants and pulmonary function of adult males living in two different air pollutant zones of Kolkata. Methods Air pollution data of two ambient air quality monitoring stations located at Rabindrabharati and Victoria Memorial was collected from West Bengal Pollution Control Board, Kolkata for the period from January to March 2012. Study was conducted on 200 males (17-22 yrs), subdivided into two groups from living within 3 km radius of that two monitoring stations. They were investigated for their spirometric lung functions following method and technique recommended by American Thoracic Society. Results were expressed as mean ± SD and independent samples T test was conducted to compare between groups. Results PM10, SO2 concentrations were significantly higher in Rabindrabharati zone, whereas no significant differences were noted in NO2 and CO concentrations though values were higher at Rabindrabharati than Victoria Memorial. FVC, FEV1 , FEF25-75%, MVV were significantly lower in males of Rabindrabharati zone. Conclusion Exposure to high air pollutant concentration might be associated with reduced pulmonary function in adult males. Kathmandu University Medical Journal Vol.13(1) 2015; 24-28